OPTIMALISASI PENGELOLAAN ZAKAT DI INDONESIA - Drs. Syahrul (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
Zakat is maaliyah ijtima'iyyah worship, it means worship the field of property that has a very important position in the development of society If the charity is well managed, both retrieval and distribution by applying modern management functions, God willing, will be able to raise the welfare of society. Therefore in the Qur'an and hadith, many command to tithe, as well as praise for those who do, both in this world and in the hereafter. Conversely, there are many verses of the Qur'an and the Hadith the prophet who denounces those who are reluctant to do so, as well as a threat to their world and hereafter. By him that the need for professional management of zakat by the institution that is trusted and managed by zakat (amil) trustworthy, honest, and professional